2015
DOI: 10.1002/rcm.7424
|View full text |Cite
|
Sign up to set email alerts
|

Water circulation and governing factors in humid tropical river basins in the central Western Ghats, Karnataka, India

Abstract: The narrow coastal strip to the west of the Western Ghats displays unique water characteristics in both tropical river basins investigated. For the smaller and hilly Swarna basin, the dense vegetation (wet canopies) could largely re-evaporate the (intercepted) rain, leading to no marked seasonal or altitude effect on the water isotope values within the basin. The larger Nethravati basin, which stretches farther into the foothills of the Western Ghats, receives winter monsoon water, and thus exhibits a clear se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…We also calculated percentage of freshwater input into MZ estuary using d 18 O values measured in the Swarna river basin, which is in proximity to the MZ estuary that receives discharge from the river originating from the Western Ghat Mountains. The average d 18 O of river water during the month of November was À2.67% (Tripti et al 2016). Assuming the end member river water composition, our estimates yielded freshwater Cuxes for the month of July until January, varying from 72% to 12%, which is slightly different from the estimate described earlier in the text.…”
Section: Estimation Of Freshwater Cuxcontrasting
confidence: 61%
“…We also calculated percentage of freshwater input into MZ estuary using d 18 O values measured in the Swarna river basin, which is in proximity to the MZ estuary that receives discharge from the river originating from the Western Ghat Mountains. The average d 18 O of river water during the month of November was À2.67% (Tripti et al 2016). Assuming the end member river water composition, our estimates yielded freshwater Cuxes for the month of July until January, varying from 72% to 12%, which is slightly different from the estimate described earlier in the text.…”
Section: Estimation Of Freshwater Cuxcontrasting
confidence: 61%
“…The δ 2 H data compiled for the precipitation and surface water over the Indian subcontinent shows homogenous signature in southern part with relatively higher isotope ratio (δ 2 H > -20 ‰) than the north and northeast India due to larger influence of southwest monsoon (Hobson et al, 2012). The initial analysis on impact of climatic conditions on water budgeting and local moisture recycling in the central part of the Western Ghats through stable isotopes of rainwater, river water and groundwater have been reported in our earlier study (Tripti et al, 2016). This study is carried out to provide a spatial monitoring of water isotopes on a synoptic scale of the Western Ghats to account for the hydrological budgeting and monsoonal climate along the humid tropical high mountains.…”
Section: Motivationmentioning
confidence: 56%
“…These studies have reported that the precipitation of higher amount exhibits lower stable isotope ratio due to enrichment of lighter isotopes whereas the lower precipitation amount exhibits higher stable isotope ratio due to enrichment of heavy isotopes. However, this difference in the stable isotope ratios with precipitation amount tends to be smaller in the tropical ecosystems (Scholl et al, 2009;Tripti et al, 2016) although there is a large variability in precipitation amount. There are also studies reporting the reversed rainfall amount effect on the stable isotope ratios (i.e., a positive correlation of δ 18 O and δ 2 H with precipitation amount) of precipitation in the tropical region (Yadava et al, 2007).…”
Section: Historical Background and Current Status Of Knowledgementioning
confidence: 92%
See 2 more Smart Citations